Maximal independent sets in graphs with cyclomatic number at most two - Li, Shuchao; Jing, Wei (Utilitas Mathematica, 2010)
In this paper, we determine the largest number of maximal independent sets among all connected graphs on n vertices with cyclomatic number c, for c ≤ 2. We also characterize those extremal graphs achieving the maximum values.